Towards a Generation of Religious Moderation Through Natural and Social Sciences in Primary Schools: Opportunities and Challenges - Jaka Pasa Tribrata; Sekar Purbarini Kawuryan; Tarisa Jayanti (Jurnal Penelitian Pendidikan IPA, 2025)
This research is based on the government's efforts to improve harmony between Indonesian communities through religious moderation. So, this research was conducted to identify the challenges and opportunities faced in implementing religious moderation through learning natural sciences and social studies in elementary schools. Elementary schools play a strategic role in fostering moderate character through the integration of tolerant values, especially in the natural sciences and social sciences learning curriculum. The preparation of this article uses a literature review. The results of the study show that learning natural and social sciences has an important role and is a forum in forming a moderate generation. The natural sciences develop critical and objective thinking to prevent fanaticism, while the social sciences teach social diversity and how to coexist with a pluralistic society. However, this is accompanied by challenges such as teachers' lack of understanding of religious moderation. In conclusion, religious moderation is important for Indonesian people to live in harmony, this can be realized through teaching from elementary school through collaborative learning in natural sciences and social sciences learning. Meanwhile, training with nuances of religious moderation for teachers is an option to add insight in carrying out learning practices with students.